A Single Point Mutation in the Mumps V Protein Alters Targeting of the Cellular STAT Pathways Resulting in Virus Attenuation - Tahir Malik; Laurie Ngo; Trent Bosma; Steven Rubin (Viruses, 2019)
Mumps virus (MuV) is a neurotropic non-segmented, negative-stranded, enveloped RNA virus in the Paramyxovirus family. The 15.4 kb genome encodes seven genes, including the V/P, which encodes, among other proteins, the V protein. The MuV V protein has been shown to target the cellular signal transducer and activator of transcription proteins STAT1 and STAT3 for proteasome-mediated degradation. While MuV V protein targeting of STAT1 is generally accepted as a means of limiting innate antiviral responses, the consequence of V protein targeting of STAT3 is less clear. Further, since the MuV V protein targets both STAT1 and STAT3, specifically investigating viral antagonism of STAT3 targeting is challenging. However, a previous study reported that a single amino acid substitution in the MuV V protein (E95D) inhibits targeting of STAT3, but not STAT1. This provided us with a unique opportunity to examine the specific role of STAT 3 in MuV virulence in an in vivo model. Here, using a clone of a wild type MuV strain expressing the E95D mutant V protein, we present data linking inhibition of STAT3 targeting with the accelerated clearance of the virus and reduced neurovirulence in vivo, suggesting its role in promoting antiviral responses. These data suggest a rational approach to virus attenuation that could be exploited for future vaccine development.